A relação entre os processos especializados de alfabetização de cegos e sua utilização/interferência na sala regular - Soares, Antonio Francisco (2020)
This research aimed to describe and analyze the procedures used in the basic literacy of the blind, through the Braille system, used by the Specialized Center and in the pedagogical work carried out in the regular classroom. It is based on the perspective of language studies that distinguish basic literacy, such as the mastery of written language whose form of representation differs from oral language of the write language, and literacy, such as its social use, from the person who participates in the literate worldwide, making constant, continuous and growing use in all its social practices. Considering that, in Brazil, little has been investigated about these processes, the detailed description and analysis of the different procedures were organized in three axes (preparatory activities, Braille teaching activity and activities for exploring school content), with data collected through audio recordings and field records, whose transcripts were organized in scenes that detail the relationship between specialized teachers and students, in the Specialized Educational Service, as well as those developed in the classroom, seeking to verify the relationship established between these two teaching loci. The main findings refer to the extreme complexity of the activities for the development of the tactile perception necessary for the constitution of an efficient reader, the previous experiences of life as facilitators or hinders of this learning and, despite the existence of some integrated activities, the little relationship between specialized activities and pedagogical work in the classroom